Sustainable development through effective project management: the Petromasila in Yemen - Al-Zubaidi, Razi; Ariffin, Mohd Khairol; Ismail, Mohd Idris Shah; Ahmad, Kamarul Arifin; Raqee, Ali; Abdulsamad, Akram (Scholar Publishing, 2023)
This study examines the process by which the components of project management influence the sustainable development effectiveness of PetroMasila personnel in Yemen. The quantitative technique was utilized in the current investigation. The online survey was utilized to gather information from 342 workers working in departments involved in project-related activities. The Structural Equation Model (SEM) was used in Smart-PLS Software to analyze the data. This study revealed that project management and its following aspects, including planning management and cost management had a substantial and favorable impact on the oil industry's capacity for sustainable growth. The study model explained 32% of the variance in sustainable development effectiveness. In addition, this paper outlines limitations and further research.